Understanding the Decision to Sell a Home in South Africa - Runge, Kurt (School of Management Studies, 2026)
With various factors compounding competition in the real estate agency environment in South Africa, such as PropTech and the consequent disruptions to core business models, it is important that a study of the home seller is conducted to provide agencies with cutting-edge research to enhance their marketing strategies. To this end, this study aims to understand the behaviour of selling a home in South Africa. After establishing that the Theory of Planned Behaviour (TPB) would be the best-suited behavioural model, the theoretical gaps in knowledge that began to emerge were that, to the best of the researcher's ability, none of the prior literature in real estate using TPB dealt with selling a home, and none examined respondents who resided in South Africa. Therefore, the first research question of this study asks whether the TPB can be applied to the real estate environment with respect to selling a home. And the second research question asks what factors influence the decision to sell a home from the lens of this theoretical framework. An online survey was conducted using the database of the South African real estate agency Leadhome and the staff at the University of Cape Town (UCT) to improve the response rate and collect a sample of 175 respondents. Partial Least Squares Structural Equation Modelling (PLS-SEM) was the chosen statistical model employed. It was found that the attitude of the potential home seller has an impact on their intention, so real estate agencies should rather pursue leads who are happy to sell their homes. This could be achieved by generating marketing material that promotes the benefit of selling a home, which then resonates with those who have a positive attitude about potentially selling their home. It was also found that if influential individuals were supportive of the decision, the individual had a higher intention to sell their home. Therefore, marketing messaging should concentrate on what might resonate well with parents and other influential family members. The study showed that South Africans who intend to sell their home want to feel in control of the process. Therefore, marketing messaging may prove more effective if shown to support home sellers through the process.